Dampak Aplikasi Tiktok Terhadap Kebudayaan Indonesia - Aqilla Lajnah Panayitsa; Panji Al Falah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
The development of digital technology has brought about major changes in the dynamics of Indonesian culture. One of the most prominent social media platforms is TikTok, which offers a creative space for its users to promote local arts, traditions, languages, and cultural heritage. This study aims to analyze the impact of TikTok on Indonesian culture, both positively and negatively. Positively, TikTok helps preserve local culture through short videos featuring traditional dances, culinary specialties, and the use of regional languages. This platform also supports the introduction of Indonesian culture to a global audience, increasing awareness of the younger generation about the importance of local culture. However, on the other hand, TikTok raises challenges such as cultural homogenization due to the dominance of global trends, distortion of traditional cultural elements, and the erosion of local values. Through a qualitative approach with literature studies, this study found that TikTok has great potential as a tool for cultural preservation if used wisely. In conclusion, collaboration is needed between content creators, the community, and the government to maintain a balance between preserving local culture and digital modernity.